Haunting prison : exploring the prison as an abject and uncanny institution - Fredriksson, Tea (Emerald studies in culture, criminal justice and the arts., 2023)
"Through the study of ten commercial published prison autobiographies, Haunting prison: exploring the prison as an abject and uncanny institution unveils how prison is narrativized and socially represented as an abject and uncanny institution, shedding new light on what prison is and does in Western carceral imaginations"--